Sistemska administracija v Linuxu - Fister, ml., Iztok; Fister , Iztok (2023)
System Administration in Linux. This book is intended for beginners who want to acquire the basic knowledge and skills needed to manage the Linux operating system, as well as for experienced system administrators who want to refresh their knowledge. The book is divided into thematically organised chapters that start with an introduction to Linux and gradually delve deeper into its basic components. Readers will learn how to write Bash scripts, harness the power of sed and awk scripts, manage users efficiently, optimise disks and file systems, and configure network resources. The book includes numerous real-world examples that provide practical insights and reinforce the concepts covered. Whether a beginner or an experienced administrator, this book provides clear and pragmatic knowledge for mastering Linux administration.
Keywords: Linux operating system; system administration; script programming; sed; awk